Insuring the unknown. (December 2015) - Parsons, C
Uncertainty is the central element in insurance. This article examines how insurers evaluate and price risks that can present very high levels of uncertainty, and which many underwriters regard as especially hazardous in insurance terms. These are the risks associated with new medical devices, new pharmaceutical products and others substances for human consumption, such as food additives. Insurance is likely to be needed for these products both during their research and development phases, including insurance for clinical trials, and also once the device, drug or other substance gains approval and is in regular use. The article examines the types of insurance that are available to cover these risks, the organizations that provide insurance and how the insurance is organised. It discusses the basic principles that insurers use to price insurance before considering the difficulties presented by novel and complex risks generally. The article concludes with a description of the techniques that insurers employ to analyse and price the particular risks that are our subject and a discussion of how underwriters seek to overcome the special problems associated with them.